2006
DOI: 10.1063/1.2209205
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the IR reflectance LO absorption bands on the crystalline texture of AlN films

Abstract: The infrared reflectance spectra of polycrystalline sputtered AlN films are analyzed in relation to their crystalline texture. AlN films with perfect c-axis orientation and good piezoelectric response exhibit a single peak at 887cm−1 corresponding to the A1–longitudinal-optical (LO) vibrational mode. However, {0001}-textured films with traces of 101̱1, 101̱2, and 101̱3 reflections in their x-ray diffraction patterns show an additional peak at 905cm−1 that we assign to an E1-A1 quasi-LO mode due to interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…3), and a multiple impurity band centred at around 2150 cm − 1 was observed as well. This band is typically present in PECVD AlN films only [13,[19][20][21][22], where the 2150 cm − 1 has been attributed in the past to the stretching of the Al-N 2 [13] or to the Al-H or Al-C`N [19,20]. By comparing this impurity band, after absorbance normalization by thickness and background, a decrease of the area could be observed in films with larger average grain size (see Figs.…”
Section: Plasma-injector Distancementioning
confidence: 93%
“…3), and a multiple impurity band centred at around 2150 cm − 1 was observed as well. This band is typically present in PECVD AlN films only [13,[19][20][21][22], where the 2150 cm − 1 has been attributed in the past to the stretching of the Al-N 2 [13] or to the Al-H or Al-C`N [19,20]. By comparing this impurity band, after absorbance normalization by thickness and background, a decrease of the area could be observed in films with larger average grain size (see Figs.…”
Section: Plasma-injector Distancementioning
confidence: 93%
“…Numerous studies have employed Raman scattering and far-infrared ͑IR͒ spectroscopies to investigate several physical properties of GaN, AlN, and the ternary alloy AlGaN such as their phonon modes, the crystal quality and the orientation of the as-grown material, free-carrier effects, and the piezoelectric response. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] It is now clear that the longitudinal optic ͑LO͒ phonons ͓A 1 ͑LO͒ and E 1 ͑LO͔͒ of hexagonal AlGaN display a one-mode behavior, whereas the rest of the Raman or IR active phonon modes ͓E 2 , A 1 ͑TO͒ and E 1 ͑TO͔͒ exhibit a two-mode behavior. 13,17 Similarly, it has been shown that the LO and transverse optic ͑TO͒ phonons of cubic AlGaN exhibit one-mode and two-mode behaviors, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1,[4][5][6][7][8][9][12][13][14][15] In contrast, only a few works reported IR transmission measurements, 3,9,12,18 most of which were performed in normal-incidence configuration. Reports dealing with oblique-incidence IR transmission to study the phonons of group-III nitrides are scarce.…”
mentioning
confidence: 99%
“…Because these two modes are polar, they split into longitudinal optical (LO) and transverse optical (TO) components, which appear at around 900 and 660 cm -1 , respectively. According to Snell's law of diffraction, and considering the directions of the bonds related to the Al and El modes, under normal incidence the reflectance spectra of A1N films containing only (00-2)-oriented grains exhibit a single Al(LO) mode, whereas films containing tilted grains show, addi- tionally, the El(LO) mode [22]. Fig.…”
Section: Structural and Piezoelectric Characterization Of Aln Filmsmentioning
confidence: 99%